#TheDress: The Role of Illumination Information and Individual Differences in the Psychophysics of Perceiving White–Blue Ambiguities. (23rd April 2016) - Hesslinger, Vera M.; Carbon, Claus-Christian
In early 2015, a public debate about a perceptual phenomenon that impressively demonstrated the subjective nature of human perception was running round the globe: the debate about #TheDress, a poorly lit photograph of a lace dress that was perceived as white–gold by some, but as blue–black by others. In the present research ( N = 48), we found that the perceptual difference between white–gold perceivers ( n 1 = 24, 12 women, M age = 25.4 years) and blue–black perceivers ( n 2 = 24, 12 women, M age = 24.3 years) decreased significantly when the illumination information provided by the original digital photo was reduced by means of image scrambling (Experiment 1). This indicates that the illumination information is one potentially important factor contributing to the color ambiguity of #TheDress—possibly by amplification of a slight principal difference in psychophysics of color perception which the two observer groups showed for abstract uniformly colored fields displaying a white–blue ambiguity (Experiment 2).